Combat PTSD and Implicit Behavioral Tendencies for Positive Affective Stimuli: A Brief Report - Clausen, Ashley N.; Youngren, Westley; Sisante, Jason-Flor V.; Billinger, Sandra A.; Taylor, Charles; Aupperle, Robin L. (Frontiers in Psychology, 2016)
Background: Prior cognitive research in PTSD has focused on automatic responses to negative affective stimuli, including attentional facilitation or disengagement and avoidance action tendencies. More recent research suggests PTSD may also relate to differences in reward processing, which has lead to theories of PTSD relating to approach-avoidance imbalances. The current pilot study assessed how combat-PTSD symptoms relate to automatic behavioral tendencies to both positive and negative affective stimuli. Method: Twenty male combat veterans completed the Approach-Avoidance Task (AAT), Clinician Administered PTSD Scale, Beck Depression Inventory-II, and State-Trait Anger Expression Inventory-II. During the AAT, subjects pulled (approach) or pushed (avoid) a joystick in response to neutral, happy, disgust, and angry faces based on border color. Bias scores were calculated for each emotion type (avoid-approach response latency differences). Main and interaction effects for psychological symptom severity and emotion type on bias score were assessed using linear mixed models. Results: There was a significant interaction between PTSD symptoms and emotion type, driven primarily by worse symptoms relating to a greater bias to avoid happy faces. Post-hoc tests revealed that veterans with worse PTSD symptoms were slower to approach as well as quicker to avoid happy faces. Neither depressive nor anger symptoms related to avoid or approach tendencies of emotional stimuli. Conclusion: PTSD severity was associated with a bias for avoiding positive affective stimuli. These results provide further evidence that PTSD may relate to aberrant processing of positively valenced, or rewarding stimuli. Implicit responses to rewarding stimuli could be an important factor in PTSD pathology and treatment. Specifically, these findings have implications for recent endeavors in using computer-based interventions to influence automatic approach-avoidance tendencies.